(untitled) (Research, Society and Development, 2021)
The social pressure to be thin has caused millions of adolescents, mostly females, to use inappropriate methods, such as self-induced vomiting and excessive physical exercise to achieve the standard of beauty idealized by the media. This spread of this pattern has been identified as one of the causes of eating disorders in adolescents. This paper reviews the literature on non-purgative bulimia nervosa, discussing its causes, effects and nutritional therapy.